GeoMAREA: A Gamma‐ray spectrometer for in‐situ marine environmental applications - Tsabaris, Christos; Androulakaki, Effrosini G; Patiris, Dionisis L; Maragos, Fotis; Eleftheriou, Georgios; Pappa, Filothei K; Alexakis, Stylianos; Kokkoris, Michael; Vlastou, Roza (HNPS Advances in Nuclear Physics, 2020)
A new medium resolution (based on a 2″x2″CeBr3 crystal) gamma-ray spectrometer named “GeoMAREA” was developed and applied for measuring radioactivity in aquatic environments. The system is capable for qualitative and quantitative measurement of radionuclides in aquatic environments with maximum depth of deployment up to 600 m. A special software is developed to fulfill different demands of the end-users in order to: a) provide real time data using the cable mode, b) perform communication tasks with a data center transferring (near) real time data, c) provide time series in sequential buffers for continuous monitoring in a stand-alone mode and d) provide profile data and subsequently maps using mobile vehicles (underway mode). The spectrometer was calibrated first using point sources for energy, energy resolution and efficiency. The system offers activity concentrations of all detected gamma-ray emitters in Bq/m3 using the marine efficiency calibration, which is reproduced via the MCNPX code [1]. Two experimental points were used for validation of the theoretical estimation obtained by two reference sources (137Cs and 40K) diluted in a water-filled tank. Currently, GeoMAREA is deployed in a closed aquatic system where groundwater discharges (Anavalos, Kiveri, Greece). A first estimation of the intrinsic background of the crystal at the emission energy area of 40K is estimated. Additionally, an inter-comparison exercise with the low resolution system KATERINA II [2], is also described.